15 Safety of Human Chorionic Gonadotropin Monotherapy for Men with Previous Exogenous Testosterone Use or Replacement Therapy. Issue 1 (1st April 2022) - Rainer, Q; Pai, R; Masterson, T
ABSTRACT: Introduction: Human chorionic gonadotropin (hCG) is homologous to luteinizing hormone (LH) and stimulates endogenous testosterone (T) production and may be an option for testosterone replacement therapy (TRT). Currently, hCG is recommended for hypogonadal men with fertility concern as it prevents azoospermia seen with exogenous testosterone use. It is unknown if hCG is as efficacious as T in improving symptoms. We hypothesized that hCG is an effective and safe treatment in males with a history of exogenous T use or TRT. Objective: Our objective was to evaluate for changes in symptoms and side effects to assess hCG monotherapy as a possible method of TRT in adult males with a history of previous exogenous T use or TRT. Methods: We retrospectively reviewed 50 charts using exogenous T (including testosterone cypionate, clomid, anastrozole, methandienone, and testosterone gel) and were switched to hCG monotherapy for at least 1 month with follow-up labs. We evaluated changes in hormones [T, LH, follicle stimulating hormone (FSH), and estradiol], hematocrit (HCT), glycated hemoglobin (A1c), and prostate specific antigen (PSA). Results presented as means standard deviation. Student t-test was used to compare pre- and post-treatment values, significance was set at p=0.05. We also evaluated for incidence of thromboembolic events, including stroke, deep vein thrombosis, and myocardial infarction. Results: The average age was 43.3±10.2 years with a BMI of 29.4±3.9 kg/m2. Of the patient's reviewed, 46% had used clomid, 18% T cypionate, 15% anabolic steroids, 13% T gel, 4% T pellets, and 4% methandienone. Average follow-up after starting hCG therapy was 163 days, range 28 to 583 days. Average weekly hCG dosage was 2435 IU. Serum T experienced no significant change, from 402.54±281.34 ng/dL to 404.29 ±259.64 ng/dL (p=0.58, n=50). No change was seen in FSH (4.82±6.21 to 3.71±3.24 mIU/mL, n=25), LH (3.12±4.18 to 1.98±1.86 mIU/mL, n=25), PSA (0.79±0.39 to 0.64±0.25 ng/mL, n=6), estradiol (27.84±14.82 to 27.96±13.18 pg/mL, n=31), or A1c (5.51±0.41 to 5.41±0.0.43 %, n=8). There was a statistically significant decrease of HCT (45.05±4.87 to 43.91±4.48 %, n=15). When evaluated for improvement of erectile dysfunction (ED, n=30), low libido (n=30), and low energy (n=32), 57%, 63%, and 66% of patients reported improvement of each symptom, respectively. Only 41% of patients with ED were noted to be on another medication or therapy specifically for ED. No thromboembolic events were observed. Conclusions: Weekly hCG dosing appears to have no significant effect on T levels in men with a history of exogenous T use or TRT. The majority of patients reported an improvement in their hypogonadal symptoms. No changes were noted in PSA and A1c. HCT was noted to have a small, but statistically significant decrease and no thromboembolic events were recorded. Disclosure: No